2003
DOI: 10.1002/mrm.10399
|View full text |Cite
|
Sign up to set email alerts
|

A correlative measure for processing multiangle diffusion‐weighted images

Abstract: A simple metric for the shared diffusion anisotropy between two voxels is proposed. The metric has large values when the diffusion is highly anisotropic in both voxels and oriented in the same direction. This metric can be used in several ways, three of which are illustrated in this article. First, the metric can be used to rapidly calculate a fractional anisotropy measure using an arbitrary number of measured diffusion values. Second, a simple way to exploit the metric for filtering DWI data with neighboring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Unlike the analysis presented in the current study, these methods all involve intensive offline processing. More recent studies (36, 37) (which were published while this manuscript was under review) also reported that the icosahedral encoding scheme can provide anisotropy estimates using the DW data. The current work presents a comprehensive theoretical and experimental analysis, and a detailed comparison between the DW‐ and tensor‐based approaches.…”
Section: Discussionmentioning
confidence: 87%
“…Unlike the analysis presented in the current study, these methods all involve intensive offline processing. More recent studies (36, 37) (which were published while this manuscript was under review) also reported that the icosahedral encoding scheme can provide anisotropy estimates using the DW data. The current work presents a comprehensive theoretical and experimental analysis, and a detailed comparison between the DW‐ and tensor‐based approaches.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, it has been previously shown that IVOH can be detected already at b-values as low as 1000 s/mm 2 (Tuch et al, 2002). The combination of the 63 directions used in the present study and a b-value of 1000 s/mm 2 has Table 1 Summary of the indices of anisotropy used in this study: fractional anisotropy (Basser and Pierpaoli, 1996), geodesic anisotropy (Batchelor et al, 2005), GAA (Pipe and Farthing, 2003), cumulative residual entropy (Chen et al, 2005), generalised anisotropy and scaled entropy (Ozarslan et al, 2005).…”
Section: Simulated Datamentioning
confidence: 87%
“…A model free approach to characterization of anisotropy was proposed by Pipe and Farthing (2003). Their definition is based on a simple correlative metric, G(A,B), for the anisotropy shared between voxels A and B (see the supplementary material for more detail).The proposed anisotropy index was called GAA because it is calculated from the correlative metric between a voxel and itself, G(A,A).…”
Section: Introductionmentioning
confidence: 99%
“…An overview of the diffusion-based MRI metrics is provided in Supplementary Table 2 . Diffusion-weighted images were processed to obtain maps of fractional anisotropy, axial diffusivity, mean diffusivity, radial diffusivity, normalised eigenvalue ratio ( Armitage and Bastin 2000 ), volume fraction ( Alexander et al 2000 ), scaled relative anisotropy ( Conturo et al, 1996 , Kingsley and Monahan, 2005 ), ultimate anisotropy scaled to the diffusion ellipsoid volume, surface area, or both (UA vol , UA surf , and UA vol,surf ) ( Ulug and van Zijl, 1999 , Kingsley and Monahan, 2005 ), ellipsoidal area ratio ( Xu et al, 2009 , Kang et al, 2010 ), gamma variate anisotropy ( Armitage and Bastin 2000 ), G AA ( Pipe and Farthing, 2003 , Correia et al, 2011 ), geodesic anisotropy ( Batchelor et al, 2005 , Correia et al, 2011 ), and local diffusion homogeneity ( Gong and Zang, 2013 ). The diffusion metric maps were transformed to patient T1 space using a 6 degrees of freedom affine transformation ( Jenkinson et al 2002 ).…”
Section: Methodsmentioning
confidence: 99%